APPLIED MATHEMATICS AND MODELING - Toshtemirov, J.M (Educational Research in Universal Sciences, 2023)
Cast your mind back to school physics or chemistry and you’re likely to recall a certain amount of mathematics involved. Boyle’s law (relating pressure and volume of a gas), the law of gravity, Newton’s second law (relating force, mass, and acceleration) — all mathematical formalisms of laws underpinning the world around us.